DESCRIPTION OF THE POTENTIAL OF SOME DIVE SPOTS ON LEMBEH BITUNG ISLAND - Alma Karangan Pongtuluran; Margresye Diana Rompas (HOSPITALITI DAN PARIWISATA, 2023)
Tourism in Indonesia has complex assets to be managed better, one of which is marine tourism. Many areas in Indonesia have attractive tourism potential so that they can be developed into marine tourism objects. Marine tourism includes matters related to tourism, pleasure and recreation activities carried out in coastal areas and marine waters. One of the areas in Indonesia that has great potential in marine tourism is North Sulawesi. North Sulawesi has several tourist destinations that are in great demand by both foreign and local tourists. The potential for marine tourism in North Sulawesi which is quite promising to be developed besides Bunaken Island in Manado City is in Bitung City, precisely on Lembeh Island. Lembeh Island is one of the choices of tourist destinations that are sought after by diving and snorkeling lovers because of the beauty of underwater tourism. The charm of Lembeh Island is used as a destination for foreign and local tourists to just relax or dive with the beauty of its sea spots. The natural beauty of the sea is able to attract foreign and local tourists to come and enjoy it.